DEVELOPMENT OF A PARTICIPATORY WORKSHOP-BASED LEARNING MODEL FOR FOSTERING COMMUNITY POTTERY INNOVATION - Ruayruay, Wassa; Kaewdee, Chatchai (Journal of MCU Nakhondhat, 2026)
The objectives of this research were to: 1) investigate the context of problems, body of knowledge, and needs regarding the creation of OTOP community pottery innovations in Nakhon Si Thammarat Province; 2) develop and validate the appropriateness of a participatory action learning model for creating community pottery innovations; and 3) implement the model and evaluate its effectiveness on learners' pottery innovation competencies. This study employed a Research and Development (R&D) methodology consisting of four steps: 1) problem investigation; 2) model development and validation by experts; 3) model implementation; and 4) evaluation. The experimental sample group consisted of 25 students majoring in Industrial Arts, selected via purposive sampling. Quantitative data were analyzed using descriptive statistics and t-tests. The research findings indicated that: 1) the most critical community problem was the lack of successors due to disinterest among the younger generation, coupled with products having limited, outdated designs that failed to meet market demands; 2) the developed participatory action learning model (CP-I) comprised four steps (C-P-I-R) and was assessed as having the highest level of appropriateness (IOC = 0.94); and 3) the implementation results revealed that learners’ innovation creation competencies were significantly higher after the intervention than before at the .05 level ( = 16.89), with a very high effect size (Cohen’s = 3.38). Additionally, satisfaction with the model was at the highest level ( = 4.57). Consequently, this participatory action learning model for creating community pottery innovations serves as a vital tool in bridging education with community development to foster innovators and sustainably preserve local wisdom.